KONSEP WAHDATU SYUHUD MENURUT MUHAMMAD SAID RAMADHAN AL BUTHI DALAM SURAH AN NUR AYAT 35 - Harahap, Raja Halomoan Sahilun (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
ABSTRACT The essence of tauhid, or the oneness of God, is reflected in human awareness of Allah’s omnipotence experienced through everyday life, which shapes deep faith and love. This awareness leads humans to constantly remember and feel Allah’s presence in their hearts, bringing peace and tranquility in life and death. This essence forms the core of dhikr and the concept of Wahdatu Syuhud as the true meaning of tauhid. This study employs a library research method with a qualitative approach, utilizing primary and secondary sources collected through literature review and documentation. The data are analyzed descriptively and analytically to produce systematic and valid insights. The results reveal three types of humans based on their awareness and belief in divinity. First, those who believe in God based on suggestion and information without critical observation. Second, those who focus on scientific discoveries without acknowledging the existence of God, often driven by egoism and personal interests. Third, those who balance scientific knowledge with religious faith, recognizing their limitations as creations of Allah and making this belief the foundation of their life and worship. The third type is considered the best because they harmoniously integrate reason and heart, making them worthy leaders and caretakers of the universe. ABSTRAK Hakikat tauhid atau pengesaan Tuhan tercermin dalam kesadaran manusia terhadap kemahakuasaan Allah yang dirasakan melalui pengalaman sehari-hari, sehingga membentuk keyakinan dan kecintaan yang mendalam. Kesadaran ini menjadikan manusia selalu mengingat dan merasakan kehadiran Allah dalam hati, yang membawa ketenangan dan ketentraman dalam hidup dan mati. Esensi ini menjadi inti dari zikir dan konsep Wahdatu Syuhud sebagai hakikat tauhid. Penelitian ini menggunakan metode kepustakaan dengan pendekatan kualitatif, memanfaatkan sumber primer dan sekunder yang dikumpulkan melalui studi pustaka dan dokumentasi. Data dianalisis secara deskriptif dan analitis untuk menghasilkan pemahaman sistematis dan valid. Hasil penelitian mengungkap tiga tipe manusia berdasarkan tingkat kesadaran dan keyakinannya terhadap ketuhanan. Pertama, manusia yang percaya pada ketuhanan berdasarkan sugesti dan informasi tanpa pengamatan kritis. Kedua, manusia yang fokus pada penemuan ilmiah tanpa mengakui keberadaan Tuhan, sering kali didasari egoisme dan kepentingan pribadi. Ketiga, manusia yang mampu menyeimbangkan ilmu pengetahuan dengan keyakinan religius, mengakui keterbatasan diri sebagai ciptaan Allah dan menjadikan keyakinan tersebut sebagai landasan hidup dan pengabdian. Tipe ketiga ini dianggap sebagai manusia terbaik karena mampu memadukan akal dan hati secara harmonis, sehingga layak menjadi pemimpin dan pengelola alam.